Risk factors and preventive strategies for post-traumatic stress disorder in neonatal intensive care unit - Maria Di Chiara; Gianluigi Laccetta; Sara Gangi; Benedetta De Santis; Caterina Spiriti; Martina Attenni; Laura Bertolaso; Giovanni Boscarino; Maria Chiara De Nardo; Gianluca Ciambra; Pasquale Parisi; Gianluca Terrin (Frontiers in Psychology, 2022)
BackgroundPreterm birth and admission to the neonatal intensive care unit (NICU) could induce post-traumatic stress disorder (PTSD). PTSD is an important factor to focus on, as it is associated with parental mental health difficulties and with changes in caregiving quality such as increased intrusiveness, reduced sensitivity, and increased attachment insecurity for the child.AimsWe aimed to study the main risk factors, in the early life of newborns, and preventive measures for PTSD in parents of neonates hospitalized in the NICU.MethodsWe included parents of preterm newborns, consecutively admitted to the NICU of the University La Sapienza of Rome. The presence of PTSD following preterm birth and NICU admission was assessed using the Clinician-administered PTSD scale (CAPS) at enrollment and at 28–30 days following NICU admission or the moment of discharge. We also evaluated the Family Environment Scale which measures the social environment of all types of families; the Parental Stressor Scale which measures parental anxiety and stress; the Spielberger State-Trait Anxiety Inventory consisting of two parts measuring the State (response to present situation) and Trait (pre-disposition to be anxious) anxieties separately, and the Beck Depression Inventory Second Edition assessing depressive symptoms.ResultsWe found, in a multivariate analysis, that the gestational age of newborns admitted to NICU significantly (β = 2.678; p = 0.040) influences the occurrence of PTSD. We found that the cases showed significantly (β = 2.443; p = 0.020) more pathological Parental Stressor Scale sights and sounds scores compared to controls. The early Kangaroo-Care (KC) significantly (β = −2.619; p = 0.015) reduces the occurrence of PTSD.ConclusionPost-traumatic stress disorder in parents of preterm newborns is a pathological condition that should be properly managed, in the very first days after birth. The NICU environment represents a main risk factor for PTSD, whereas KC has been demonstrated to have a protective role in the occurrence of PTSD.